Thymoquinone effects on dopamine level and lactate dehydrogenase activity in differentiated SH-SY5Y cells exposed to amphetamine - Nurul Farah Aina Md Fauzi
Amphetamine (AT) is used to treat some medical conditions and also known to be abused recreationally. It is a potent central nervous system stimulant that is capable of producing damaging effects to the central dopaminergic pathway. Most of AT users are treated clinically for symptomatic treatment which is associated with neurological side effects. To date, there is growing interest in naturally occuring compunds which have lesser side effects to treat health problems. One of the potential compounds is thymoquinone (TQ), an active compound of Nigella sativa which is known for its cellular protective effects. Based on previous literature, there was no study on the effects of TQ in preventing damaging effects of AT. Hence, the current study is to investigate the potential of TQ to prevent damaging effects caused by AT. The objectives of this study were to determine the IC50 value of AT and TQ on differentiated SH-SY5Y neuronal cells and to evaluate the charges of dopamine (DA) levels and lactate dehydrogenase (LDH) activity in the cells exposed to AT after co-administering with TQ. Differentiated SH-SY5Y cells were grown in cell culture flask containing DMEM/F12 medium supplemented with 10% (v/v) fetal bovine serum and 1% (v/v) penisillin/streptomycin. Cell viability was manually counted using a hemocytometer to determine the IC50 value of AT and TQ. Serially diluted solutions of AT (7396, 3698, 1849, 925, 462, 231, 116 and 0 µM) and TQ (6090, 3045, 1523, 761, 381, 190, 95 and 0 µM) were added to the cells in 96-well plate and the plate was incubated for 72 hours. Subsequently, 20 µl of 3-(4,5-dimenthylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and 100 µl of dimenthyl sulfoxide were added to each well to dissolve the formazan crystals formed. The DA levels and LDH activity were determined by using the Enzyme-Linked Immunosorbent Assay (ELISA) and LDH activity assay kits respectively. Statistical analysis was conducted using one-way analysis of variance followed by Dunnet's multiple comparison tests. A P-value of less than 0.05 was considered statistically significant. The IC50 values of AT and TQ were determined to be 1596 µM respectively. Co-administration of 40 µM od AT and 30 µM of TQ demonstrated a significant increase in DA levels at 48 hours of exposure when compared to administration of AT alone. There was also a significant decrease in LDH activity in the cells exposed to both AT and TQ compared to administration of AT alone. These findings suggested that TQ has a role in maintaining the DA activity and also possesses a neuroprotective effect against cell damage after a long-term AT exposure.